Hemozoin differentially regulates proinflammatory cytokine production in human immunodeficiency virus-seropositive and -seronegative women with placental malaria - Julie M. Moore (2018)
Pregnant women are at an increased risk for malarial infection. Plasmodinm falciparum accumulates in the placenta and is associated with dysregulated immune function and poor birth outcomes. Malarial pigment (hemozoin) also accumulates in the placenta and may modulate local immune function. In this study, the impact of hemozoin on cytokine production by intervillous blood mononuclear cells from malaria-infected placentas was investigated. There was a dose-dependent, suppressive effect of hemozoin on production of gamma interferon (IFN-γ), with less of an effect on tumor necrosis factor alpha (TNF-α) and interleukin-10, in human immunodeficiency virus-seronegative (HIV-) women. In contrast, IFN-γ and TNF-α production tended to increase in HIV-seropositive women with increasing hemozoin levels. Production patterns of cytokines, especially IFN-γ in HIV- women, followed different trends as a function of parasite density and hemozoin level. The findings suggest that the influences of hemozoin accumulation and high-density parasitemia on placental cytokine production are not equivalent and may involve different mechanisms, all of which may operate differently in the context of HIV infection. Cytokine production dysregulated by accumulation of hemozoin or high-density parasitemia may induce pathology and impair protective immunity in HIV-infected and -uninfected women.